On the character tables of symmetric groups - Kawsathon, K.; Rodtes, K. (Algebra and Discrete Mathematics, 2021)
In this paper, some zeros and non-zeros in the character tables of symmetric groups are displayed in the partition forms. In particular, more zeros of self conjugate partitions beside odd permutations are heavily investigated.